Effectiveness of community-based burden estimation to achieve elimination of lymphatic filariasis: A comparative cross-sectional investigation in Côte d'Ivoire. - Hope Simpson; Daniele O Konan; Kouma Brahima; Jeanne d'Arc Koffi; Saidi Kashindi; Melissa Edmiston; Stefanie Weiland; Katherine Halliday; Rachel L Pullan; Aboulaye Meite; Benjamin Guibehi Koudou; Joseph Timothy (Public Library of Science (PLoS), 2022)
For lymphatic filariasis (LF) elimination, endemic countries must document the burden of LF morbidity (LFM). Community-based screening (CBS) is used to collect morbidity data, but evidence demonstrating its reliability is limited. Recent pilots of CBS for LFM alongside mass drug administration (MDA) in Côte d'Ivoire suggested low LFM prevalence (2.1-2.2 per 10,000). We estimated LFM prevalence in Bongouanou District, Côte d'Ivoire, using a comparative cross-sectional design. We compared CBS implemented independently of MDA, adapted from existing Ministry of Health protocols, to a population-based prevalence survey led by formally trained nurses. We evaluated the reliability of case identification, coverage, equity, and cost of CBS. CBS identified 87.4 cases of LFM per 10,000; the survey identified 47.5 (39.4-56.3; prevalence ratio [PR] 1.84; 95% CI 1.64-2.07). CBS identified 39.7 cases of suspect lymphoedema per 10,000; the survey confirmed 35.1 (29.2-41.5) filarial lymphoedema cases per 10,000 (PR 1.13 [0.98-1.31]). CBS identified 96.5 scrotal swellings per 10,000; the survey found 91.3 (83.2-99.8; PR 1.06 [0.93-1.21]); including 33.9 (27.7-38.8) filarial hydrocoele per 10,000 (PR of suspect to confirmed hydrocele 2.93 [2.46-3.55]). Positive predictive values for case identification through CBS were 65.0% (55.8-73.5%) for filarial lymphoedema; 93.7% (89.3-96.7%) for scrotal swellings; and 34.0% (27.3-41.2%) for filarial hydrocoele. Households of lower socioeconomic status and certain minority languages were at risk of exclusion. Direct financial costs were $0.17 per individual targeted and $69.62 per case confirmed. Our community-based approach to LFM burden estimation appears scalable and provided reliable prevalence estimates for LFM, scrotal swellings and LF-lymphoedema. The results represent a step-change improvement on CBS integrated with MDA, whilst remaining at programmatically feasible costs. Filarial hydrocoele cases were overestimated, attributable to the use of case definitions suitable for mass-screening by informal staff. Our findings are broadly applicable to countries aiming for LF elimination using CBS. The abstract is available in French in the S1 File.